OP37 Bacterial suppression of intestinal fungi via activation of human gut Vδ2+ T-cells. (21st January 2022) - Mathew, L; Savage, M; Pardieu, C; O'Brien, M; Sze, S K; Eberl, M; Stagg, A; Gasparetto, M; Kok, K; Lindsay, J; McCarthy, N
Abstract: Background: The human gut is colonized by diverse microbes including fungi such as Candida albicans, which has been implicated in the pathogenesis of Crohn's disease (CD). Intestinal C. albicans typically exists as commensal yeast, but can also form tissue-invasive filaments that secrete Candidalysin toxin to disrupt epithelial barriers. Commensal gut bacteria produce molecules that induce host immunity, including phosphoantigen HMB-PP which stimulates Vδ2+ T-cell homing to intestine and mucosal expression of IL-22 to promote barrier integrity. We aimed to identify mechanisms of gut barrier defence against fungal invasion in health and CD. Methods: Colonic biopsies / resected tissue were stimulated or not with HMB-PP in the presence or absence of anti-IL-22 blocking antibody and analysed by flow-cytometry / microscopy to determine extent of fungal outgrowth. Fungal isolates were identified using standard morphological and biochemical criteria before assessment of filamentation, cell wall composition, and NETosis induction. Results: Mucosal Vδ2+ T-cell activation with bacterial phosphoantigen HMB-PP, in the presence of epithelial damage-associated cytokine IL-15, potently suppressed growth of endogenous fungi in human colonic organ cultures. Vδ2-mediated fungal suppression required IL-22 and was sufficient to restrict the growth of multiple fungal species, including a range of emerging pathogenic moulds as well as archetypal pathobiont C. albicans . In Vδ2-deficient CD patients, mucosal biopsy stimulation with HMB-PP failed to control fungal growth. CD-derived C. albicans strains also displayed rapid filamentation ex vivo and higher levels of NOD2 ligand chitin than were observed in isolates from healthy controls. Comparing hypoxic with oxygenated cultures that mimic inflamed intestine, pSILAC proteomic analysis of a representative CD-derived C. albicans strain confirmed features of invasive growth (e.g. DAO1, IHD1), whereas a healthy control isolate exhibited metabolic hallmarks of symbiosis (Jen1p, SCH9). These divergent characteristics directly impacted on host anti-fungal immune responses, since the CD-derived strain rapidly induced neutrophil extracellular traps in vitro, whereas the healthy control isolate did not. Conclusion: These data suggest that commensal bacteria can activate host Vδ2 T-cells to suppress fungal invasion of the gut epithelium via an IL22-dependent mechanism that is deficient in CD patients.